3D Generation of Multipurpose Atomic Force Microscopy Tips (Adv. Sci. 27/2022). Issue 27 (23rd September 2022) - Glia, Ayoub; Deliorman, Muhammedin; Qasaimeh, Mohammad A.
Abstract : 3D Generation of Multipurpose Atomic Force Microscopy Tips In article number 2201489, Ayoub Glia, Muhammedin Deliorman, and Mohammad A. Qasaimeh report on the technology of 3D generation of multipurpose atomic force microscopy tips (3DTIPs). 3DTIPs are developed with great flexibility in material, design, integration, and function. 3DTIPs are capable of obtaining high resolution and high‐speed atomic force microscope imaging using common modes, well suited for various applications in air and liquid, and can significantly stimulate advances in various fields. 3DTIPs might serve as a milestone in advancing scanning probe microscopy from a mire common imaging tool towards an evolved platform integrable with broader research applications.